Preparation of ZnO nanostructures by RF-magnetron sputtering on thermally oxidized porous silicon substrate for VOC sensing application. (January 2015) - Al-Salman, Husam S.; Abdullah, M.J.
Abstract : Graphical abstract: Highlights: Porous structures were introduced to ZnO by using a thermally oxidized PS. The sensitivity of the ZnO/oxidized PS was 83.4% for 22 ppm of ethanol gases. High porosity, and abundant oxygen vacancies enhanced the sensing. The sensor showed favorable selectivity for ethanol over acetone. Abstract: ZnO nanostructures were grown on thermally oxidized porous silicon (PS) substrates by RF-magnetron sputtering for volatile organic compounds (VOCs) sensing applications. PS was fabricated by electrochemical anodization of n-type crystalline silicon in an ethanoic hydrofluoric acid solution to produce a PS surface. X-ray diffraction (XRD) analysis confirmed that the ZnO nanostructure highly preferred an (0 0 2) phase orientation. The sensitivities of the ZnO/oxidized PS sensor investigated for 22 ppm of acetone, ethanol, iso-propanol, and toluene vapor at the optimum operating temperature of 250 °C were 79.6%, 83.4%, 69.3%, and 69%, respectively. The ZnO/oxidized PS sensor can be detect VOC vapor up to 2 ppm.